On the Formation of the Clergy - Rabanus Maurus, Archbishop of Mainz, 784?-856 (Book collections on Project MUSE., 2023)
"Blessed Hrabanus Maurus (also called Rabanus Maurus) was born in Mainz and grew up in the monastery of Fulda (both in what is now Germany). He taught in the monastery's school, then became the Abbot of the monastery, and subsequently was appointed as the Archbishop of Mainz. He wrote prolifically on theological subjects. His goal in De institutione clericorum (On the Formation of Clergy) was to accomplish educational reform for the training and enlightenment of men studying for the priesthood. He was concerned not only with promoting formal theological studies but also with cultivating the development of preaching style as well as pastoral sensitivity in counseling Catholic laity. He died in 856. The original language of this book is Latin"--